Strain differences in Blastocystis isolates as detected by a single set of polymerase chain reaction primers - Init, I.; Mak, J.W.; Lokman Hakim, S.; Yong, H.S. (1999)
A total of 20 isolates of Blastocystis were characterized using a single set of polymerase chain reaction (PCR) primers. The amplification product revealed five types of pattern. All four isolates from Singapore yielded PCR products quite different from those of the local isolates. However, most of the local isolates showed a major product at either 280 or 500 bp, or both. We also suspected that the amplification product detected at 280 bp might be an indicator of the pathogenicity of this parasite. One isolate (M12) obtained from a monkey showed patterns similar to those of human isolates (10203 and KP1) and probably belongs to the same strain. The results indicate that the intraspecific or interstrain variations in these 20 Blastocystis isolates belong to 5 different patterns. The differences among isolates of the same strain revealed by the presence or absence of certain amplification products showed further intrastrain variations in this parasite.